Legumain in Acute Coronary Syndromes: A Substudy of the PLATO (Platelet Inhibition and Patient Outcomes) Trial - Ida Gregersen; Annika E. Michelsen; Ngoc Nguyen Lunde; Axel Åkerblom; Tatevik G. Lakic; Mona Skjelland; Karolina Ryeng Skagen; Richard C. Becker; Johan Lindbäck; Anders Himmelmann; Rigmor Solberg; Harald T. Johansen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background The cysteine protease legumain is increased in patients with atherosclerosis, but its causal role in atherogenesis and cardiovascular disease is still unclear. The aim of the study was to investigate the association of legumain with clinical outcome in a large cohort of patients with acute coronary syndrome. Methods and Results Serum levels of legumain were analyzed in 4883 patients with acute coronary syndrome from a substudy of the PLATO (Platelet Inhibition and Patient Outcomes) trial. Levels were analyzed at admission and after 1 month follow‐up. Associations between legumain and a composite of cardiovascular death, spontaneous myocardial infarction or stroke, and its individual components were assessed by multivariable Cox regression analyses. At baseline, a 50% increase in legumain level was associated with a hazard ratio (HR) of 1.13 (95% CI, 1.04–1.21), P=0.0018, for the primary composite end point, adjusted for randomized treatment. The association remained significant after adjustment for important clinical and demographic variables (HR, 1.10; 95% CI, 1.02–1.19; P=0.013) but not in the fully adjusted model. Legumain levels at 1 month were not associated with the composite end point but were negatively associated with stroke (HR, 0.62; 95% CI, 0.44–0.88; P=0.0069), including in the fully adjusted model (HR, 0.57; 95% CI, 0.37–0.88; P=0.0114). Conclusions Baseline legumain was associated with the primary outcome in patients with acute coronary syndrome, but not in the fully adjusted model. The association between high levels of legumain at 1 month and decreased occurrence of stroke could be of interest from a mechanistic point of view, illustrating the potential dual role of legumain during atherogenesis and acute coronary syndrome. Registration URL: https://www.clini​caltr​ials.gov; Unique identifier: NCT00391872.